Current state of the government bond market in the Russian Federation - M. N. Lakoza (Путеводитель предпринимателя, 2020)
The article reveals the main current trends of the government bond market in the Russian Federation. Various factors that influence the state bond market were studied. External factors included geopolitical risks, rating actions, monetary policy of world Central banks, and the dynamics of oil prices. The main internal factors were: lower inflation, the Bank of Russia’s monetary policy, the return of non–residents to Russian ruble debt, the strengthening of the ruble, the Bank of Russia’s policy in terms of banking regulation, and the flexible policy of initial placement of Federal loan bonds. In 2019, external factors did not have a primary impact on the Russian government securities market, but they determined the General background of investor relations. The market was largely influenced by internal factors.